Induction of labour using Foley catheter : traction versus no traction, a randomised controlled trial at Hospital Tengku Ampuan Afzan, Kuantan - Siti Mariam binti Ismail (Kulliyyah of Medicine, International Islamic University Malaysia, 2016)
Induction of labour can be achieved by placement of a transcervical Foley catheter. The aim of this study was to assess the effectiveness of 750 ml traction on Foley catheter for labour induction. Randomised controlled trial performed on pregnant women at 37- 41 week who were admitted for induction of labour with unfavourable cervix. They were randomly assigned into two groups, Foley's with 750 ml traction and foley without traction. The outcome measured were change in Bishop score, outcome of delivery, successful vaginal birth after cesarean section, pain score and risk of maternal and fetal infection. 160 women were randomised into traction group (n=80) and control group (n=80). The mean change in Bishop score was similar in both groups. Traction group had significantly (p=0.006) higher number of vaginal delivery (70%) compared to control group (49%). The rate of successful VBAC was also significantly (p= 0.001) higher in the traction group. Participants were comfortable using both methods with low pain score. There was no different in neonatal outcomes and risk of maternal infections in both groups. In conclusion, application of traction resulted in more vaginal deliver and successful VBAC.